Educational Game Media Based on CAI in PPKn for Fourth Grade Elementary School - Kartika Eka Mustika Yani; Parji; Candra Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The implementation of PPKn learning is still fixated on conventional methods, and the lack of interactive learning media that utilizes technology in elementary schools makes students feel bored. Most elementary school students have difficulty understanding PPKn material because they tend to perceive PPKn as a subject with a lot of memorization, especially on the history of the formulation of Pancasila. The rapid development of technology is expected teachers to be able to bring up innovation in Pancasila and Civic Education learning to increase student learning motivation. This study aims to develop learning media, namely educational game media based on Computer Assisted Instruction (CAI) material, on the history of the formulation of Pancasila in PPKn learning for fourth-grade elementary school students. The type of research used by researchers is development research or R&D with the ADDIE development model. Observation, interview, questionnaire, and documentation methods were used for data collection in this study. Quantitative and qualitative techniques are helpful as data analysis techniques. Based on the validation results of media experts, a percentage of 84.5% met the very feasible criteria, material experts obtained a percentage of 100% completed the very feasible criteria, as well as user responses, namely student responses, obtained an average score of 93% meeting very feasible criteria and response teachers obtained a percentage of 96.2% very feasible criteria. So it can be concluded that educational game media based on CAI is appropriate to be used as PPKn learning media for fourth-grade elementary school students.